2020
DOI: 10.1186/s12943-020-01236-z
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of super-enhancer-driven tumor suppressor gene RCAN1.4 expression promotes the malignancy of breast carcinoma

Abstract: Background: Super-enhancers (SEs) play a crucial role in cancer, which is often associate with activated oncogenes. However, little is known about how SEs facilitate tumour suppression. Individuals with Down syndrome exhibit a remarkably reduced incidence of breast cancer (BC), moving the search for tumor suppressor genes on human chromosome 21 (HSA21). In this study, we aim to identify and explore potential mechanisms by which SEs are established for tumor suppressor RCAN1.4 on HSA21 in BC. Methods: In silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…SEs are occupied by various transcription factors, cofactors, and histone modifications ( Whyte et al, 2013 ; Khan and Zhang, 2019 ; Deng et al, 2020 ). Compared with TEs, SEs can not only promote gene transcription more efficiently ( Bae et al, 2016 ) but also regulate cell-type-specific gene regulatory networks ( Hnisz et al, 2013 ), define cell identity and contribute to the development of diseases ( Niederriter et al, 2015 ; Kang et al, 2020 ) such as neuroblastoma ( van Groningen et al, 2017 ) and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SEs are occupied by various transcription factors, cofactors, and histone modifications ( Whyte et al, 2013 ; Khan and Zhang, 2019 ; Deng et al, 2020 ). Compared with TEs, SEs can not only promote gene transcription more efficiently ( Bae et al, 2016 ) but also regulate cell-type-specific gene regulatory networks ( Hnisz et al, 2013 ), define cell identity and contribute to the development of diseases ( Niederriter et al, 2015 ; Kang et al, 2020 ) such as neuroblastoma ( van Groningen et al, 2017 ) and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of key TFs is of great significance to the research of super-enhancers. According to the method of Deng et al 38 to identify TFs, we analyzed E1 component enhancer region and EphA2 core promoter region that bind to TFs and enriched with H3K27ac, H3K4me1 and H3K4me3 from ChIP-seq of ENCODE project. Among the 340 TFs of ENCODE project, we found that 115 TFs bind to the E1 component enhancer region, which overlaps with the region characterized by the enrichment of H3K27ac and H3K4me1 markers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, they are deregulated in many human cancers. Along with them, lncRNAs derived from the transcription of active enhancers are differentially expressed in cancer tissues and have been revealed to act as oncogenes, promoting the transcriptional activation of the oncogenic pathways and even inducing chromosomal rearrangements and genomic instability [ 115 , 116 , 117 , 118 ].…”
Section: Transcriptional Gene Modulation By Lncrnasmentioning
confidence: 99%